Kontribusi Pembelajaran Tasawuf Terhadap Pembentukan Keperibadian Islam Pada Generasi Muda - Mohamad Fahri Haikal; Miftah Rama N; Mardiansyah; Saidul Fahmi; Fahmi Alfiani; Ismail Mubarok (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the relevance of Sufism values in character education in the digital era. The research uses a qualitative approach with a library research method. Data were obtained from books, scientific journals, and works of Sufism figures relevant to the topic, then analyzed using content analysis techniques. The results show that Sufism values such as sincerity, patience, trust in God (tawakal), and self-reflection (muhasabah) play an important role in shaping students’ character and can become a solution to the moral crisis in the digital era. Therefore, the integration of Sufism values into Islamic education can help create a generation that is characterized, religious, and possesses strong moral resilience.